Analysis of the causes of cracks in marble slabs in a large-surface floor of a representative commercial facility. (March 2019) - Hoła, Jerzy; Sadowski, Łukasz; Nowacki, Andrzej
Abstract: The paper analyzes the causes of cracking in marble slabs that are embedded in the large-surface floor of a representative commercial building. In the case of many such objects, these slabs are laid on a concrete substrate and start cracking a short time after the start of operation. The "nature" of the occured cracks is presented, and the results of testing the adhesion between the marble slabs and concrete substrate using non-destructive impulse response and impact-echo methods, the results of strength tests of the marble slab specimens that were taken for laboratory tests, and also the results of visiual inspections of the concrete substrate are provided. These results were then related to the technology of laying marble slabs, and on this basis the causes of cracking were diagnosed while explaining their mechanism. The presented test results and analysis will be useful for people that implement and supervise works related to the execution of stone slab floors, in particular marble floors, with regards to an increase of the quality of such floors and the elimination of the causes of their cracking. Highlights: The paper analyses the causes of cracking in marble slabs, The slabs were embedded in the floor of a representative commercial building, The results of testing the adhesion between the slabs and substrate were presented, The causes of cracking were diagnosed and the mechanism was explained, The analysis will be useful for engineers that supervise the execution of slab floors.